PENERAPAN TERAPI RELAKSASI BENSON TERHADAP TINGKAT INSOMNIA PADA LANSIA DI RUANG AKAR WANGU RSUD PANDAN ARANG BOYOLALI - Utami, Linda Tri; Hartutik, Sri; Widodo, Panggah (JURNAL KESEHATAN KARTIKA, 2023)
Background : Insomnia is a phenomenon that often occurs in the elderly, changes in sleep patterns in the elderly are caused by aging, female gender, marital status, smoking habits, consumption of caffeinated drinks, medical factors, psychological pressure and noise so that non-pharmacological management is needed one of which is benson relaxation therapy. Objective : To find out the application of benson relaxation therapy to the level of insomnia in the elderly in the vetiver room at Pandan Arang Boyolali Hospital. Method : Implementation was carried out using the case study method to 2 respondents, according to the inclusion and exclusion criteria, the research instrument used the IRS (Insomnia Rating Scale) questionnaire for the level of insomnia and Benson's Relaxation SOP, for 3 consecutive days a day for 30 minutes in the morning day. Results : Based on the results of the implementation that has been done, there is a decrease in the level of insomnia before and after the benson relaxation therapy is done. Conclusion : Benson relaxation therapy can be used as a non-pharmacological technique or independent intervention in patients with insomnia.